ЦИФРОВАЯ ЭКОНОМИКА: ОСОБЕННОСТИ ФОРМИРОВАНИЯ И ТЕНДЕНЦИИ РАЗВИТИЯ - A. A. Alimbaev; B. S. Bitenova (Экономика: стратегия и практика, 2019)
The concept on «Industry 4.0» involves creating digital technologies and development of new technologies-based digital society.Digitization and intensification of processes is a necessity for a modern economy in all spheres of human life. Digitalization affects industry, government, health care, education, logistics and other areas.The advent of digital technologies has accelerated due to the intensive technological changes posed by the penetration of digital technologies into every aspect of our life and being widely accepted have modified it. ICT innovations had a considerable impact not only on citizens’ behavior, their information needs but how they work and exchange information. Further advancement of digital innovation particularly cloud, mobile services and artificial intelligence will greatly enhance this modification and provide us with exclusive services and prosperity that have not previously been expected. Digitalization blurs the boundaries, in consequence of which there is a permanent connection of societies at the international level.The approaches to the definition of the concepts «digital technology» and «digital economy» are being analyzed in this article.The article writers point to the investigations of different researchers’ attitudes and offer their own definition to the concept of «digital economy». The major priority is focused on the State Program «Digital Kazakhstan», its goals, content and importance to meet socio-economic development goals of the country.The aim of the article is to study the existing theories and practical-methodological approaches of the digital economy, and on this basis to justify the conditions for the formation and development trends of the digital economy in the Republic of Kazakhstan.